2006
DOI: 10.1111/j.1365-2621.2005.tb08301.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Under Ultraviolet Light on the Shelf Life of Fresh-Cut Cantaloupe Melon

Abstract: : The effect of processing cantaloupe melon under ultraviolet‐C (UV‐C) radiation on storage properties of the cut fruit at 10 °C was compared with post‐cut UV‐C fruit treatment and the untreated control. Cutting fruit under UV‐C light induced a hypersensitive defense response that resulted in increased accumulation of ascorbate peroxidase relative to the other 2 treatments. Fruit processed under UV‐C radiation had the lowest esterase activity throughout the storage period. Lipase activity was higher in post‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 40 publications
(19 reference statements)
3
45
0
5
Order By: Relevance
“…PPO and POD showed similar behavior throughout the experiment, this agreed with Richard-Forget and Gauillard (1997) that the role of POD in enzymatic browning in apples is highly correlated to PPO activity. Ascorbic acid as a reducing agent was able to decrease the pH or sequestrated metal ions in the product and thus was able to prevent enzymatic browning for some period of time (Jang and Moon 2011;Lamikanra et al 2005;Wang et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…PPO and POD showed similar behavior throughout the experiment, this agreed with Richard-Forget and Gauillard (1997) that the role of POD in enzymatic browning in apples is highly correlated to PPO activity. Ascorbic acid as a reducing agent was able to decrease the pH or sequestrated metal ions in the product and thus was able to prevent enzymatic browning for some period of time (Jang and Moon 2011;Lamikanra et al 2005;Wang et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…A hypersensitive defense response in fresh-cut cantaloupe melon was induced by a continuous UV-C treatment, resulting in increased accumulation of POD. In addition, the results showed that reduced lipase activity in UV-C-treated samples during storage and other induced antisenescence defense responses appeared to reduce rancidity and improve firmness retention in the stored fruit (Lamikanra et al 2005). …”
Section: Solid Foods Of Vegetable Originmentioning
confidence: 94%
“…It does not require chemicals or heat, and is not expensive. Presently, UV radiation technology is used as an alternative to chemical sterilization in food products (Lamikanra, Kueneman, Ukuku, & Bett-Garber, 2005), and UV-C (wavelength of 220-300 nm with 90% of emission at 253.7 nm) has been approved by the FDA for use on food products to control surface microorganisms (US Food, 2007 Within the UV-C range, inactivation studies using the 253.7 nm light energy have been shown to be effective in reducing pathogenic bacteria and spores in vegetables (Allende & Artés, 2003) and fruits (González-Aguilar, Wang, Buta, & Krizek, 2001). However, few studies have been conducted on the application of UV-C irradiation to chicken products.…”
Section: Introductionmentioning
confidence: 99%